2009
DOI: 10.1021/ac901871d
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of H2S Using Gold Nanoparticle Decorated Single-Walled Carbon Nanotubes

Abstract: Herein, we demonstrate that highly sensitive conductometric gas nanosensors for H 2 S can be synthesized by electrodepositing gold nanoparticles on single-walled carbon nanotube (SWNT) networks. Adjusting the electrodeposition conditions allowed for tuning of the size and number of gold nanoparticles deposited. The best H 2 S sensing performance was obtained with discrete gold nanodeposits rather than continuous nanowires. The gas nanosensors could sense H 2 S in air at room temperature with a 3 ppb limit of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(127 citation statements)
references
References 39 publications
4
123
0
Order By: Relevance
“…Despite low and positive values of the Gibbs free energies of H 2 S adsorption on the external wall of (5,0) and (5,5) nanotubes, the adsorption energies are negative. It confirms no interaction between H 2 S gas and nanotube [15]. For obtaining more information, the optical properties under rotation of H 2 S molecule and natural bond orbital (NBO) analysis of H 2 S fluid-nanotube systems are studied.…”
Section: Thermodynamic Parametersmentioning
confidence: 59%
See 1 more Smart Citation
“…Despite low and positive values of the Gibbs free energies of H 2 S adsorption on the external wall of (5,0) and (5,5) nanotubes, the adsorption energies are negative. It confirms no interaction between H 2 S gas and nanotube [15]. For obtaining more information, the optical properties under rotation of H 2 S molecule and natural bond orbital (NBO) analysis of H 2 S fluid-nanotube systems are studied.…”
Section: Thermodynamic Parametersmentioning
confidence: 59%
“…Wei et al [14] demonstrated that multi-walled carbon nanotubes have extraordinarily highcurrent carrying capacity, sustaining current densities greater than 109 A/cm 2 . These novel electrical properties have generated substantial interest in utilizing carbon nanotubes in nanoelectronics [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that functionalization with metal 1 3 nanoparticles, play a crucial role in producing gas sensors with high sensitivity [19][20][21][22][23][24][25][26][27][28]. Different experimental and theoretical studies have been performed for functionalization of carbon nanotubes and graphene, with metal nanoparticles, as the gas sensor [29][30][31][32][33][34][35]. For example, Yoosefian theoretically showed that intrinsic single wall carbon nanotube (SWCNT), cannot adsorb NH 3 gas molecules suitably, but SWCNT functionalized with palladium (Pd), facilitate adsorption of NH 3 gas, leading to the high selectivity and fast response of the device [33].…”
Section: Introductionmentioning
confidence: 99%
“…43 Several industrial processes generate a huge amount of H 2 S, including natural gas processing, petroleum refining, coal gasification, biogas fermentation, and the activity of petrochemical plants, Kraft mills, and coke ovens. 43 During the process of the biogas fermentation, a huge amount of H 2 S is produced [44][45][46] because the biogas must be purified from H 2 S. Inhaled H 2 S is very harmful and can cause death depending on the concentration and the exposure duration. From the above, it is clear that the adsorption of H 2 S on graphene is a very important problem.…”
Section: Introductionmentioning
confidence: 99%